A review of eminence of scientometric indicators in scientific research productivity. Issue 2 (3rd July 2017) - Wani, Zahid Ashraf; Zainab, Tazeem
Abstract : The evaluation and assessment of scientific research output is essential to determine its success, eminence, growth and development of an individual or an institution. A reasonable and unbiased research assessment should reflect the diversity and impact of research output. In this background, productivity and quality of scholarly content offer a strong foundation for its pragmatic evaluation. The citations along-with the number of scientific publications are primarily used to evaluate research content. With the passage of time, the field of metric sciences emerged to evaluate and assess scholarly content. These have come up with desired indexes and indicators that have become integral to the evaluation process. The science indicators, in this context, are of great importance as they offer researchers, research organizations, funding agencies etc. with an empirical measure to evaluate the performance of research output. In this milieu, an endeavor is made to review the literature on the various aspects of scientometric indicators.